THE CORRELATION BETWEEN CRITICAL THINKING SKILLS AND CRITICAL READING SKILLS OF THE ENGLISH EDUCATION STUDY PROGRAM STUDENTS OF SRIWIJAYA UNIVERSITY - Rahma Dianti (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2015)
Critical thinking skill is one of the most crucial life skills that should be possessed by the students. The objectives of this study were: (1) to find out whether or not there was a significant correlation between student’s critical thinking and critical reading skills, (2) to know the student’s level of their critical thinking skills, (3) to know the student’s level of critical reading skills, (4) to find out the contribution of each aspect of critical thinking skills toward each aspect of critical reading skills, (5) to seek the mean difference of student’s critical thinking skills based on their gender, and (6) to seek the mean differences of student’s critical reading skills based on their gender. This research was conducted using correlational research design. In collecting the data, there were two tests administered in this study, those were CAAP for Critical Thinking Test and the SAT for Critical Reading skills. The population of this study consisted of 170 undergraduate students of English Education Study Program of Sriwijaya University in Bukit Besar campus in the academic year 2011/2012. 114 out of 170 undergraduate students became the samples of this study who were chosen using proportionate stratified random sampling technique based on the student’s gender. Based on the data collected and the analyses applied in this study, the findings revealed that (1) the student’s level of critical thinking skill was in the level of analysis, (2) the students were categorized as poor in critical reading skills, (3) there was a significant and positive correlation between student’s critical thinking and critical reading skills with r-value 0.713, (4) only two out of three aspects of critical thinking –analysis and evaluation- that contributed the influence toward each aspect of critical reading skills, (5) there was no mean difference between male and female students toward their critical thinking skills, and (6) there was no mean difference between male and female students toward their critical reading skills.